WaterCom: Connecting research configurations with practical deployments: A multilevel, multipurpose underwater communications test platform - MCGOLDRICK, CIARAN (ACM, 2016)
This paper describes the ongoing evolution of the Water-Com framework developed as part of the NSF funded Ocean-TUNE CRI project. A particular challenge for connecting global researchers and the public with remote, autonomous underwater research infrastructures is that translating and bringing the requesters topology and system properties into physical existence through dynamic reconfigurability of the deployed experimental infrastructure and assets. Previous work described the overall WaterCom framework, system architecture and design. The extension of this system to enable graphical node topology definition and validation, and the procedure for defining, scheduling and deploying experimental configurations on remote hardware is articulated.
WUWNet 2016 - 11th ACM International Conference on Underwater Networks and Systems
WUWNet 2016
PUBLISHED
Export Date: 10 January 2017
Shanghai, China
Keywords: Water-Com framework; Water-Com framework